The travels of the prophet ibrahim: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz : New Delhi, 2004)
This story narrates the journeys of Prophet Ibrahim as he seeks truth and spreads the message of monotheism. It highlights his unwavering faith and determination to follow God's guidance, inspiring young hearts to trust in their beliefs.